The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1590/s0080-62342003000400006
|View full text |Cite
|
Sign up to set email alerts
|

A prescrição médica eletrônica em um hospital universitário: falhas de redação e opiniões de usuários

Abstract: This study analyzed the writing failure of the computerized physician order entry system and its advantages and disadvantages according to users. At a university hospital 1,351 physician orders were analyzed and 84 nursing and medical professionals were interviewed. The results showed that 17.7% of the orders presented measures, medication had been suspended in 16.8%, in 28.2% there was dubious or misleading information and in 25% medication had been prescribed manually. The professionals indicated advantages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
20

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 15 publications
(14 reference statements)
1
9
0
20
Order By: Relevance
“…The interruption of prescriptions was the most common change found in this study and it occurred at all hospitals, including hospital A. This data was confirmed by the literature that demonstrated that interruptions of the drug regimen were not reduced by electronic prescriptions 35,39 . So, Lesar 28 highlighted the need to confirm prescription changes or interruptions, from the discussion between the pharmacist and physician.…”
Section: Changes and Types Hospitalssupporting
confidence: 87%
See 2 more Smart Citations
“…The interruption of prescriptions was the most common change found in this study and it occurred at all hospitals, including hospital A. This data was confirmed by the literature that demonstrated that interruptions of the drug regimen were not reduced by electronic prescriptions 35,39 . So, Lesar 28 highlighted the need to confirm prescription changes or interruptions, from the discussion between the pharmacist and physician.…”
Section: Changes and Types Hospitalssupporting
confidence: 87%
“…It may cause confusion, which goes against the Brazilian medical ethics code which establishes that the doctor is responsible for prescribing clearly and legibly and, therefore, without erasures 40 . Despite this, previous studies showed that erasures are common in Brazilian prescriptions 13,20,35 . Sometimes a 'free text' feature can be used to substitute erasures in prescriptions.…”
Section: Changes and Types Hospitalsmentioning
confidence: 94%
See 1 more Smart Citation
“…Erasures have also been identified to affect patient safety because they may cause misreading of information included in the prescription (3,9) .…”
Section: Influence Of the Writing Of The Medical Orders On The Adminimentioning
confidence: 99%
“…An appropriate medication prescription is key for preventing these events because ambiguous, illegible or incomplete prescriptions as well as non-harmonized nomenclature of drug prescribed (brand vs. generic name), use of abbreviations and erasures are all well-known factors that can be associated with adverse events (2)(3) . Studies have showed that the administration of medication at different times than what was prescribed is the most common adverse event during the administration step (4)(5) .…”
Section: Introductionmentioning
confidence: 99%